Synthesis and Characterization of Mononuclear Nickel Complexes with Dithiolate Ligands - Gao, Wei; Shi, Bo (Asian Journal of Chemistry, 2015)
Treatment of the mononuclear nickel complex (dppf)NiCl2 (1) [dppf = 1,1'-bis(diphenylphosphino)ferrocene] with HSCH2CH2SH or HSCHMeCHMeSH in the presence of Et3N in CH2Cl2 afforded the corresponding nickel dithiolate complexes (dppf)Ni(SCH2CH2S) (2) and (dppf)Ni(SCHMeCHMeS) (3) in 44 and 59 % yields, respectively. The new complexes 2 and 3 were structurally characterized by 1H NMR, 31P{1H} NMR and 13C{1H} NMR spectroscopy.